"Triple locks" on soil organic carbon exerted by sphagnum acid in wetlands. (15th December 2021) - Zhao, Yunpeng; Liu, Chengzhu; Wang, Simin; Wang, Yiyun; Liu, Xiaoqing; Luo, Wanqing; Feng, Xiaojuan
Abstract: Sphagnum acid, a major phenolic metabolite of Sphagnum mosses, is considered to play a key role in the remarkable accumulation of organic matter in Sphagnum -dominated wetlands. However, while previous studies have mainly focused on the antimicrobial property of Sphagnum metabolites, the effects of sphagnum acid on other soil biogeochemical processes related to soil organic carbon (SOC) stabilization are poorly investigated. Here we employ a series of incubation experiments involving sphagnum acid amendment into natural wetland soils and artificial reaction systems to comprehensively evaluate potential pathways driving SOC stabilization by sphagnum acid. We show that sphagnum acid greatly enhances the reductive dissolution of ferric iron [Fe(III)] (hydr)oxides in both wetland soils and synthetic Fe(III)-organic matter complexes, induces the formation of amorphous and poorly-crystalline Fe(III) and increases Fe-bound organic carbon. Furthermore, sphagnum acid quenches hydroxyl radicals produced by Fenton reactions during redox oscillations and indirectly suppresses the activity of phenol oxidase and β-glucosidase by inhibiting microbial activity, acidification and increasing enzyme sorption to newly formed Fe(III). Hence, sphagnum acid exerts "triple locks" on SOC through (i) Fe protection of organic matter, (ii) radical quenching, and (iii) microbial suppression. These important but under-investigated pathways are all closely related to Fe transformation, highlighting the key role of Sphagnum metabolite–Fe–organic matter interactions in regulating wetland soil carbon sinks. Changing distribution of Sphagnum under climate change and human activity will have cascading effects on soil Fe species, microbial activity and SOC stabilization, which warrants further investigation in the attempt to protect and increase wetland soil carbon stocks.